Anti-Bourgeois Media in the Japanese Proletarian Literary Movement - Takashi Wada (Humanities, 2022)
The Marxist and socialist ideas that spread throughout the world following the Russian Revolution of 1917 were also influential in bringing about changes in art and culture. Proletarian literature, which flourished in Japan in the 1920s and 1930s, was one such example. However, due to Japan’s particular historical circumstances, Japanese proletarian literature was in an ambivalent position between revolutionary literature by left-wing intellectuals and proletarian literature by and for the proletarian class in the pure sense. This article examines the chaos and friction implied by the term “proletarian” from three perspectives: the relationship between proletarian media and bourgeois media, the media distribution system, and the boundary between writers and readers. Through this examination, it clarifies that the approaches of Japanese proletarian media, while imitating bourgeois media to some extent, were unique in their potential to transform the boundary between writers and readers.